COMPARATIVE ANALYSIS OF MONEY MARKET AND CAPITAL MARKET PERFORMANCE IN INDONESIA: A CASE STUDY ON THE IMPACT OF MONETARY POLICY - Abdul Azim Wahbi; Syahrudi (Journal of Economic and Economic Policy, 2026)
Objective: This study aims to analyze the comparison of the performance of the money market and the capital market in Indonesia with a focus on the impact of monetary policy. Method: Using literature study and library research methods, this study found that the money market is more responsive in the short term to changes in monetary policy, while the capital market shows a more sustainable long-term impact. Results: The monetary policy implemented by Bank Indonesia, particularly thru the benchmark interest rate instrument (BI Rate/BI-7DRR), open market operations, and macroprudential policies, significantly affects the movements of the money market and the capital market. The results of this study provide implications for investors, regulators, and market participants to understand the sensitivity of both markets to the dynamics of monetary policy. In conclusion, monetary policy has an impact on the performance of the money market and the capital market in Indonesia, although with different response patterns. Novelty: Indonesia's financial market has two main pillars, namely the money market and the capital market. Both function as financial intermediation platforms, but they have different characteristics, instruments, and sensitivities to monetary policy.